The who, where, and what of rapid sequence intubation: prospective observational study of emergency RSI outside the operating theatre. Issue 3 (22nd April 2004) - Reid, C; Chan, L; Tweeddale, M
Abstract : Background: Emergency rapid sequence intubation (RSI) performed outside the operating room on emergency patients is the cornerstone of emergency airway management. Complication rates are unknown for this procedure in the United Kingdom and the factors contributing to immediate complications have not been identified. Aims: To quantify the immediate complications of RSI and to assess the contribution made by environmental, patient, and physician factors to overall complication rates. Methods: Prospective observational study of 208 consecutive adult and paediatric patients undergoing RSI over a six month period. Results: Patients were successfully intubated by RSI in all cases. There were no deaths during the procedure and no patient required a surgical airway. Patient diagnostic groups requiring RSI are described. Immediate complications were hypoxaemia 19.2%, hypotension 17.8%, and arrhythmia 3.4%. Hypoxaemia was more common in patients with pre-existing respiratory or cardiovascular conditions than in patients with other diagnoses (p<0.01). Emergency department intubations were associated with a significantly lower complication rate than other locations (16.9%; p = 0.004). This can be explained by the difference in diagnostic case mix. Intubating teams comprised anaesthetists, non-anaesthetists, or both. There were no significant differences in complication rates between these groups. Conclusions: RSI has a significant immediate complication rate, although the clinical significance of transient events is unknown. The likelihood of immediate complications depends on the patient's underlying condition, and relevant diagnoses should be emphasised in airway management training. Complication rates are comparable between anaesthetists and non-anaesthetists. The significantly lower complication rates in emergency department RSI can be explained by a larger proportion of patients with comparatively stable cardiorespiratory function.